Corporate ESG performance, digital transformation and climate risk disclosure - Yufei Yan; Changhao Gong; Hua Zhang (Sustainable Futures)
This paper uses the data of all listed companies in China's A-share market from 2010 to 2022, and employs textual analysis to construct climate risk disclosure indicators using corporate annual reports to validate the relationship between ESG ratings and climate risk uncertainty. Based on signaling theory, this paper explores ESG rating integration to promote corporate climate risk disclosure, stakeholder theory and resource base view to reveal the mediating roles of environmental disclosure, business credit and agency costs, and explores the moderating effects of digital transformation and managerial characteristics.The results show that: (1) Enterprises with higher ESG rating will be more active in climate risk disclosure. (2) ESG rating mainly promotes climate risk disclosure through three channels: strengthening environmental information disclosure, reducing agency costs, and improving commercial credit. In addition, digital transformation plays a moderating role in the facilitation of ESG performance to climate risk disclosure. (3) Heterogeneity analyses show that authoritative decision-making styles and CEOs with local knowledge advantages strengthen the correlation between ESG ratings and environmental and social pathways, respectively, and low-carbon pilot cities strengthen their correlation through formal institutions. On the theoretical level, this paper integrates the dual perspectives of institutional pressure and resource capacity to expand the theoretical boundaries of ESG governance; on the practical level, it provides empirical evidence for enterprises to optimise their climate disclosure strategies and for regulators to improve their ESG rating systems.